1996
DOI: 10.1108/13665629610127744
|View full text |Cite
|
Sign up to set email alerts
|

How to get feedback from your boss

Abstract: Discusses the importance of feedback to employees and how they can instigate the process. Provides details of a procedure for obtaining feedback from a reluctant boss, and supplies examples of dialogue to initiate conversations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Coates (1996) argued that to create trust, you need to establish procedures to protect participants and let everyone know what they are. Knippen (1996) has mentioned the benefits of feedback such as meeting the boss's expectations better; better performance; an employee will have to come to boss less frequently with problems, questions or decisions; or having a more satisfied employee. Steelman and Rutkowski (2004) found that employees are more inclined to develop their job performance based on unfavorable feedback when the feedback source is considered to be credible, the feedback is of high quality and the feedback is given in a thoughtful manner.…”
Section: Antecedents Of Interpersonal Trustmentioning
confidence: 99%
“…Coates (1996) argued that to create trust, you need to establish procedures to protect participants and let everyone know what they are. Knippen (1996) has mentioned the benefits of feedback such as meeting the boss's expectations better; better performance; an employee will have to come to boss less frequently with problems, questions or decisions; or having a more satisfied employee. Steelman and Rutkowski (2004) found that employees are more inclined to develop their job performance based on unfavorable feedback when the feedback source is considered to be credible, the feedback is of high quality and the feedback is given in a thoughtful manner.…”
Section: Antecedents Of Interpersonal Trustmentioning
confidence: 99%
“…In other words, there is interaction between expectations of the school leaders and monitoring to obtain collaboration between them in one way and between teachers themselves in another way. Knippen (1996) has stated that giving feedback has some advantages such as meeting what school leaders expect in the best way and improved performance; besides the need to meet the boss because of problems, questions or decisions becomes less frequent; and employees get more satisfactions.…”
Section: Introductionmentioning
confidence: 99%